The effect of nitrogen and sodium chloride stress in the productivity of some fatty acids in Chlorococcum humicola green alga - Baghdad Science Journal (مجلة بغداد للعلوم)
Algae have been considered a sources task of biofuels, which is a future alternative to fossil fuels, and this lead the environmental studies concerned with the lifting of curves or growth rates and time of replication of different kinds of algae, as well as algae cells in response to different environmental conditions, whether chemical or physical, to assess their impact on the composition of these cells and the extent of affected components that make up the living, especially fatty acid ,total fats, proteins and carbohydrates, Gbrha. Green Chlorococcum humicola showed a different response when treated with an average of agriculture Chu-10 and Chu-13 which used as control media,Compared with the degree of its response when exposed to environmental stress when remove of N or adding different concentrations of NaCl for both mentioned media, That represents a different quality and quantity of fatty acids produced inside. When Ch-10 treatment with NaCl fatty acids Palmetic, ?-liolenic and Oleic recorded marking increase as for Stearic, Linoleic and Arachidic recorded a decrease in there rates, there for In Ch-13 the acids Palmetic, Linoleic and ?-liolenic recorded significantly increase while, decreased value of Stearic acid only. When N remove from the two media, Ch-10 scored a remarkable increase in the rates of all acids except stearic acid which recorded larger decrease. Ch-13 has recorded an increase in acid values Palmetic, Linoleic and, ?-liolenic, there for stearic, oleic and Arachidic recorded less than all values in (control.) The results also showed a presence difference in curves, growth rates and replication time when the transactions mentioned